Portable thermometer - Rashmeet Kaur Chael (2023)
This thesis is a report about a portable thermometer which is a device to measure temperature and voltage at the same time. Although it is called a thermometer, it can measure voltage as well. The measured temperature and voltage will be displayed on a LCD screen. This thermometer can be carried along anywhere as it is handy and convenient. In terms of space, it consumes less space. Safety wise, it is not dangerous because the maximum power of the portable thermometer is 5 volt.